The work in the face of the implementation of the transoceanic corridor in Mato Grosso do Sul (BR) - Fernandes, Tatiane Aparecida Dreger de Souza (2024)
The Bioceanic Corridor, or Latin American Integration Route - Rila, is a road corridor aimed at integrating the Latin American and Asian territories. The discourse of the project's enthusiasts suggests a series of benefits, including economic development, improved competitiveness of productive chains, and better employment opportunities along this route. However, the lack of detailed information on how these promises will be realized and how the local population relates to or is included – in its diversity – in the project is notable. In this sense, the objective of this work is to promote a reflective debate, beyond the economistic and idealized vision of the implementation of the Bioceanic Corridor, with a spatial focus on the state of Mato Grosso do Sul, and with a focus on the issue of labor. For this purpose, this research used a literature review, with analyses based on authors from Anthropology and Geography. The results revealed that the construction of the corridor should be thought beyond the supposed "economic benefits" it may generate. Although this work concentrates the analyses on Mato Grosso do Sul, the discussions raised go beyond the borders of the state, being relevant for the entire extent of the corridor's implementation. This work draws attention to the need to consider the multiple perspectives at play in the construction of the Bioceanic Corridor, going beyond its supposed broader economic advantages.